Science Process Skills Profile of Grade V Elementary School Students: Profil Keterampilan Proses Sains Siswa Kelas V Sekolah Dasar - Iis Ariska; Fitria Eka Wulandari (Academia Open, 2021)
This study aims to reveal the profile of the science process skills of students at SD Negeri Sedatigede 2. The type of research used is survey quantitative research. The population used is 70 students. Data collection techniques using tests. The research instrument used was a test of science process skills. The test results were then analyzed using a formula and the science process skills were described into 4 categories, namely very skilled, skilled, moderately skilled, less skilled. Based on the results of the analysis, it is concluded that the research findings prove the profile of the science process skills of students in class V SD Negeri Sedatigede 2 are categorized as very skilled on the indicators of science process skills (25%-100%). The highest average value is using tools/materials (98.5%) and the lowest average value is observing (84.2%).